(untitled) (Ágora de Heterodoxias, 2019)
The following article presents the results of an investigation carried out under a qualitative approach, in which 50 employing managers were interviewed for the Business Administration career with an emphasis in Business Management and Human Resources in Costa Rica. The interviews were conducted at the end of 2017 with managers from the business sector, in Costa Rica. Initially a bibliographic review is carried out that allows contextualize the labor trend of the national and international employing market in training requirements for the careers under study; subsequently, the perception of the employing market consulted in Costa Rica is recognized and the required needs of the interviewees are realized. The results obtained are the limit of knowledge to follow when teaching the relevant training and identifies the updated needs of employers.